Cognitive Control Over Visual Motion Processing – Are Children With ADHD Especially Compromised? A Pilot Study of Flanker Task Event-Related Potentials - Lange-Malecki, Bettina; Treue, Stefan; Rothenberger, Aribert; Albrecht, Björn (Frontiers in Human Neuroscience, 2018)
Performance deficits and diminished brain activity during cognitive control and error processing are frequently reported in Attention Deficit/Hyperactivity Disorder (ADHD), indicating a “top-down” deficit in executive attention. So far, these findings are almost exclusively based on the processing of static visual forms, neglecting the importance of visual motion processing in everyday life as well as important attentional and neuroanatomical differences between processing static forms and visual motion. For the current study, we contrasted performance and electrophysiological parameters associated with cognitive control from two Flanker-Tasks using static stimuli and moving random dot patterns. Behavioral data and event-related potentials were recorded from 16 boys with ADHD (combined type) and 26 controls (aged 8 to 15 years). The ADHD group showed less accuracy especially for moving stimuli, and prolonged response times for both stimulus types. Analyses of electrophysiological parameters of cognitive control revealed trends for diminished N2-enhancements and smaller error-negativities (indicating medium effect sizes), and we detected significantly lower error positivities (large effect sizes) compared to controls, similarly for both static and moving stimuli. Taken together, the study supports evidence that motion processing is not fully developed in childhood and that the cognitive control deficit in ADHD is of higher order and independent of stimulus type.